Childhood obesity and comorbidities-related perspective and experience of parents from Black and Asian minority ethnicities in England: a qualitative study - George Obita; Mark Burns; Lawrence Achilles Nnyanzi; Chia-Hua Kuo; Noël C. Barengo; Noël C. Barengo; Ahmad Alkhatib; Ahmad Alkhatib; Ahmad Alkhatib (Frontiers Media S.A., 2024)
BackgroundPreventing childhood obesity and associated comorbidities is often hampered by disproportionate disparity in healthcare provision in minority ethnic populations. This study contextualized factors influencing childhood obesity and related comorbidity from the perspectives and experiences of parents of ethnic minority populations.MethodsFollowing ethical approval, families (n = 180) from ethnic minority populations in the Northeast of England were contacted through flyers, community social groups and online forum. Of the 180 families contacted, 22 expressed interests, of whom 12 parents were eligible to participate in the study, and one family dropped out due to time constraints. Therefore 11 parents from ethnic minority communities living with at least one child with obesity were interviewed. Each family was separately visited at home and took part in a semi-structured interview based on the study's qualitative, descriptive phenomenological design. Nine of the families had one child who was diagnosed with an obesity-related comorbidity (non-alcoholic fatty liver disease, musculoskeletal problems or respiratory disorder). Semi-structured interviews were standardized around parents' perspective and experience on how their children were impacted by obesity and comorbidities, healthcare preventative interventions including lifestyle physical activity and nutrition, and views on tackling obesity impact on their lives. All interviews were analyzed using qualitative thematic analysis.ResultsParents' perspectives revealed 11 themes centered around experience of living with a child with obesity, risks, and impact of obesity related Non-Communicable Diseases; and access to support, and barriers unique to minority ethnic groups. Parents revealed social disadvantages, fear of victimization by social services, perceptions on their cultural and religious traditions, and racial stigmatization related to their child's weight. Parents reported closer bonding with their children to protect them from the untoward consequences of overweight, and little awareness of healthcare obesity prevention programs. Work pressure, lack of time, absence of guidance from professionals were seen as barriers to healthy lifestyle, while support from friends and closer family bond in adopting healthy lifestyle behaviors were facilitators. However, there was little awareness or access to current healthcare obesity preventive offerings.ConclusionMinority ethnic communities' perspective on childhood obesity prevention does not match the healthcare system preventative offerings. Community and family-oriented obesity preventative approaches, especially lifestyle interventions are needed beyond those administered by the primary healthcare system.